THE PROBLEM OF IMPROVEMENT OF THE AVIONIC EQUIPMENT VIBRATION RESISTANCE - E. A. Danilova; C. A. Kuzina; A. V. Lysenko; V. A. Trusov; N. K. Yurkov (Научный вестник МГТУ ГА, 2017)
The article gives an approach to a solution of the problem of improvement the avionic equipment vibration resistance. It is shown that the use of the tests, which are provided by the state standards do not insure the required level of the failures caused by mechanical damages. Due to the fact that the tests are carried out restrictedly they do not completely reveal the main resonant phenomena, which define the structure vibrational strength. It is shown that the main challenges of the improvement are to increase the adequacy of test and real modes of vibration, to increase the accuracy of reproduction of the test modes on shake tables and also to increase the reliability of measuring information about the modes of vibration and dynamic responses of an object of researches and to increase the information capacity of the vibrational tests. To ensure the equivalence of the test modes to the modes of maintenance the modes of tests are provided, they are not created by in-phase submission of a test signal in points of fixing the printed circuit boards. It is shown that with the help of control over the amplitudes and phases of affecting signals on resonance frequencies the displacement of maxima deflection in the area of the printed circuit board is possible and, thereby, it is enable to increase the reliability. The received results of mathematical simulation and their correlation with the results of full-scale tests specified on the limitation of vibration tests by means of standard techniques. The conclusion about the necessity of full-scale tests modifications is drawn.